Investigation of recognition methods of a person's fatigue using a 3D camera - Bakhmet, A. G. (My University, 2018)
The object of research in the presentation is methods of analysis of image recognition. Algorithms and methods of face recognition are considered. The result of the work is the software for the analysis of human drowsiness with the help of Intel® RealSense 3D-camera.
Keywords: image recognition; analysis of human drowsiness